2013
DOI: 10.1038/nature11968
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of population epigenomic diversity

Abstract: SummaryNatural epigenetic variation provides a source for the generation of phenotypic diversity, but to understand its contribution to phenotypic diversity, its interaction with genetic variation requires further investigation. Here, we report population-wide DNA sequencing of genomes, transcriptomes, and methylomes of wild Arabidopsis thaliana accessions. Single cytosine methylation polymorphisms are unlinked to genotype. However, the rate of linkage disequilibrium decay amongst differentially methylated reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

59
711
7
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 507 publications
(785 citation statements)
references
References 42 publications
59
711
7
2
Order By: Relevance
“…In total, 9,119 genes fulfilled our criteria across the entire sample, comprising genus-wide alignments for 25 Mb of the genome. The data were analyzed together with published SNPs from 337 A. thaliana lines [2][3][4] . In total the alignment contains 7.5 million SNPs, 6.6 million of which are biallelic.…”
mentioning
confidence: 99%
“…In total, 9,119 genes fulfilled our criteria across the entire sample, comprising genus-wide alignments for 25 Mb of the genome. The data were analyzed together with published SNPs from 337 A. thaliana lines [2][3][4] . In total the alignment contains 7.5 million SNPs, 6.6 million of which are biallelic.…”
mentioning
confidence: 99%
“…Furthermore, they can be used to profile all forms of single methylation polymorphisms (SMPs). This broad coverage is important because CG-, CHG-, and CHH-SMPs accounted for 23%, 13% and 64% of all SMPs, respectively, in a natural Arabidopsis population [27].…”
Section: Msap Methods For Dna Methylation Detectionmentioning
confidence: 99%
“…This suggests a more prevalent epigenetic variation in the natural population. A recent study revealed that epigenetic variations are widespread within natural A. thaliana lines [27]. DNA methylation polymorphisms have also been observed between wild and cultivated rice [25], and between the indica and japonica subspecies of rice [23].…”
Section: Dna Methylation and Breedingmentioning
confidence: 99%
“…Recent experiments and discussion have, however, revitalized the old idea that epigenetic processes also impact on the phenotypic variation of complex traits and embryo development in inbred individuals (Biémont, 2010;Cheptou and Donohue, 2012;Vergeer et al, 2012;Schmitz et al, 2013;Liebl et al, 2013). However, further experiments are required if we are to decipher the precise mechanisms that underly the inbreeding/epigenetic relationship.…”
mentioning
confidence: 99%